Sex Work and the City The Social Geography of Health and Safety in Tijuana, Mexico - Katsulis, Yasmina (University of Texas Press, 2021)
A gateway at the U.S.-Mexico border, Tijuana is a complex urban center with a sizeable population of sex workers. An in-depth case study of the trade, Sex Work and the City is the first major ethnographic publication on contemporary prostitution in this locale, providing a detailed analysis of how sex workers' experiences and practices are shaped by policing and regulation. Contextualizing her research within the realm of occupational risk, Yasmina Katsulis examines the experiences of a diverse range of sex workers in the region and explores the implications of prostitution, particularly regarding the spheres of class hierarchies, public health, and other broad social effects. Based on eighteen months of intensive fieldwork and nearly 400 interviews with sex workers, customers, city officials, police, local health providers, and advocates, Sex Work and the City describes the arenas of power and the potential for disenfranchisement created by municipal laws designed to regulate the trade. Providing a detailed analysis of this subculture's significance within Tijuana and its implications for debates over legalization of "vice" elsewhere in the world, Katsulis draws on powerful narratives as workers describe the risks of their world, ranging from HIV/AIDS and rape (by police or customers) to depression, work-related stress, drug and alcohol addiction, and social stigma. Insightful and compelling, Sex Work and the City captures the lives (and deaths) of a population whose industry has broad implications for contemporary society at large